2008
DOI: 10.1002/chir.20597
|View full text |Cite
|
Sign up to set email alerts
|

Chirality sensing with pores: Reactive signal amplifiers for otherwise undetectable small molecules

Abstract: Recently, we have introduced a concept to determine enantiomeric excess (ee) with synthetic multifunctional pores (Tanaka and Matile, Chirality 2008;20:307-312). The reported approach is, however, limited to macromolecules and not applicable to small molecules. The problem is that the ability of synthetic pores to respond to chemical stimulation decreases with the size and the charge of the analyte. Here we demonstrate that this problem can be overcome with reactive signal amplifiers that covalently capture el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Studies with mixtures of L-and D-lactate demonstrated detectability of enantiopurities up to at least 99.6% ee. 16 This high sensitivity was in agreement with earlier results concerning the detection of extreme ee's up to 99.9975% with synthetic transport systems. 11 These results were obtained for protein biosensing a Enzymes confirmed as operational signal generators.…”
Section: Biosensingsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies with mixtures of L-and D-lactate demonstrated detectability of enantiopurities up to at least 99.6% ee. 16 This high sensitivity was in agreement with earlier results concerning the detection of extreme ee's up to 99.9975% with synthetic transport systems. 11 These results were obtained for protein biosensing a Enzymes confirmed as operational signal generators.…”
Section: Biosensingsupporting
confidence: 91%
“…45 Lactate sensing was realized with lactate oxidase as a signal generator, catalase for peroxide removal, hydrazide 50 as a signal amplifier and b-barrel pore 52 (2,4 = K,H) or polyguanidino-oxanorbornene transporters as signal transducers (Table 1, entry 16). 10,15,16 In excellent agreement with the literature, concentrations from 54 to 72 mM were determined in sour milk. 10,15 The stereoselectivity of the enzymatic signal generator provided access to chirality sensing with synthetic transport system 52 (2,4 = K,H) and amplifier 50.…”
Section: Biosensingsupporting
confidence: 85%
See 1 more Smart Citation
“…1,2 Progress made during the current period concerns modifications of staves, 131 termini 132 and internal active sites 133,134 as well as covalent capture approaches for signal amplification in sensing applications. [135][136][137][138][139][140][141] As far as the stave are concerned, replacement of the 1 3 ,2 3 ,3 2 ,4 3 ,5 2 ,6 3 ,7 2 ,8 3 -pattern in 220 with a regioisomeric 1 2 ,2 2 ,3 3 ,4 2 ,5 3 ,6 2 ,7 3 ,8 2 -motif in 221 did not disturb the formation of multifunctional b-barrel pores. 131 Attachment of tetralysine (K 4 ) tails in 222 improved pore delivery to the membrane.…”
Section: Peptide Mimicsmentioning
confidence: 97%
“…137 Enantiomer discrimination was explored for a-helices and lactate with pore 219 and the aid of proteases and lactate oxidase as enantioselective signal generators. 138,139 Signal amplification of analytes other than ketones or aldehydes was exemplified with the reaction of hydrazides such as 241 with aldehydes 246-249. 140 Inactivation of pore 223 with the resulting boronic acids could be reversed by covalent capture of catechols such as catechin 250 or epigallocatechin gallate.…”
Section: Peptide Mimicsmentioning
confidence: 99%